Home economics - British Broadcasting Corporation (London : BBC Enterprises, 1980)
This series of programmes discusses several areas of modern nutrition knowledge where health risks have been shown, and supplies relevant evidence from history, science, practical demonstrations and expert reports. There are suggestions in buying and food preparation which will guard against these risks
Backup available in VHS 1/2 in.
Keywords: Nutrition